Is Processed Food a Luxury Good in India? A Macroeconomic Engel Curve Analysis, 2007–2022 - Jai Ram Meena (Universitas Negeri Gorontalo, 2026)
Rising incomes and urbanization have substantially transformed food consumption patterns in developing economies. Patterns of food demand at the household and economy-wide levels are commonly studied in terms of changes in the structure of food demand and expenditure patterns on food items over time. This study investigates whether processed food can be considered a luxury good in India by estimating a macroeconomic Engel curve using annual data for the period 2007–2022. It uses time-series data on household final consumption expenditure incurred on purchase of processed foods and gross domestic product measured in terms of aggregate gross value added at basic prices. The data is sourced from the input-output tables of the Indian economy published by the Asian Development Bank on annual frequency. Using a log-log regression model, this study investigates whether an Engel curve exists between household final consumption expenditure on processed foods and gross value added. The results show that household final consumption expenditure on processed foods in India has grown faster than aggregate gross value added during the said period, indicating an income elasticity of demand greater than unity. This suggests that processed foods behaved as a luxury good in India during the study period. The study highlights important implications for processed food policy framing, including strategies for processed food manufacturing, input sourcing, agribusiness development, environmental sustainability, managing health risks associated with consumption of processed foods, taxation, and export promotion and management in India’s evolving food economy.